A NLP Pipeline for the Automatic Extraction of a Complete Microorganism's Picture from Microbiological Notes - Mora, Sara; Attene, Jacopo; Gazzarata, Roberta; Giacobbe, Daniele Roberto; Blobel, Bernd; Parruti, Giustino; Giacomini, Mauro (Journal of personalized medicine, 2022)
The Italian "Istituto Superiore di Sanità" (ISS) identifies hospital-acquired infections (HAIs) as the most frequent and serious complications in healthcare. HAIs constitute a real health emergency and, therefore, require decisive action from both local and national health organizations. Information about the causative microorganisms of HAIs is obtained from the results of microbiological cultures of specimens collected from infected body sites, but microorganisms' names are sometimes reported only in the notes field of the culture reports. The objective of our work was to build a NLP-based pipeline for the automatic information extraction from the notes of microbiological culture reports. We analyzed a sample composed of 499 texts of notes extracted from 1 month of anonymized laboratory referral. First, our system filtered texts in order to remove nonmeaningful sentences. Thereafter, it correctly extracted all the microorganisms' names according to the expert's labels and linked them to a set of very important metadata such as the translations into national/international vocabularies and standard definitions. As the major result of our pipeline, the system extracts a complete picture of the microorganism.
Keywords: information extraction; natural language processing; laboratory information systems; hospital-acquired infections; international coding system